2009
DOI: 10.1007/s11249-009-9426-6
|View full text |Cite
|
Sign up to set email alerts
|

Tribochemistry of a Ti Alloy Under Fretting in Air: Evidence of Titanium Nitride Formation

Abstract: The present investigation focuses on the tribological transformation occurring on a Ti alloy (Ti17) under fretting in air. Several fretting wear tests were performed on a large scale punch on plane configuration (two types of planes tested: bare Ti6242 and CuNiIn-coated Ti6242) at several temperatures from ambient up to 450°C. In all the cases, two zones were identified on the scars: a lateral oxidized rim and a highly deformed region at centre. Metallurgical observations revealed similarities with Tribologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 26 publications
(42 reference statements)
1
17
1
Order By: Relevance
“…This conclusion is quite interesting as it suggests that in the inner part of the contact, an additional N 2 partial pressure is observed which can explain and potentially quantify the exotic nitriding process observed at room temperature in the inner part of titanium fretting interfaces (Fig. 24b) [9,10,35]. Nitriding of the inner TTS, after [10] inside the scar On the other hand, by depriving oxygen and in turn increasing the concentration of nitrogen gas, such air distilling process presently modelled using ADR approach can explain the nitriding process observed in many closed fretting interfaces.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…This conclusion is quite interesting as it suggests that in the inner part of the contact, an additional N 2 partial pressure is observed which can explain and potentially quantify the exotic nitriding process observed at room temperature in the inner part of titanium fretting interfaces (Fig. 24b) [9,10,35]. Nitriding of the inner TTS, after [10] inside the scar On the other hand, by depriving oxygen and in turn increasing the concentration of nitrogen gas, such air distilling process presently modelled using ADR approach can explain the nitriding process observed in many closed fretting interfaces.…”
Section: Discussionmentioning
confidence: 77%
“…although some nitriding processes could be observed [9,35] as detailed in the following discussion (Section 6).…”
Section: Reaction Termmentioning
confidence: 92%
“…Oxygen O 1s and O 2s peaks are also detected in all the spectra, as well as a small quantity of nitrogen N 1s, around 2% of the global semi-quantification. Even if some authors [25,26] have emphasized the role of nitrogen in the formation of some tribological transformed structures on titanium alloy, here it is not the relevant element regarding the glaze layer formation, which is mainly controlled by an oxidation process. In addition, it is interesting to notice that there is no peak of aluminum showing that there is no transfer from the alumina counterface.…”
Section: Extreme Surface Chemical Analysismentioning
confidence: 98%
“…Even if this treatment usually requires high temperatures, 600-1000°C, and a long time, one can wonder if an interaction could arise on a microscopic scale where such temperatures can be locally reached. For example, when investigating fretting of a titanium alloy from 20 to 400°C in air, Mary et al 22 observed the formation of a tribologically transformed structure exhibiting a specially high nitrogen content. They highlighted that nitrogen was able to penetrate the contact and form a nanocrystalline titanium nitride phase even at low temperatures due to the energy dissipated by friction.…”
Section: Discussionmentioning
confidence: 99%